Navigating the training satisfaction effects on organizational performance: examining multiple mediating paths with PLS-SEM and IPMA - Md Nurun Nabi; Md Shelim Miah; Md Solaiman Hossain; Md Farijul Islam; Sabrin Sultana; Margia Yesmin; Enamul Hasan (Social Sciences and Humanities Open)
Drawing on Victor Vroom's expectancy theory, this study falls under the purview of research that examines the impact of training satisfaction on organizational performance. In contrast, employee work engagement and employee job satisfaction were employed as mediating roles between training satisfaction and organizational performance in the context of the textile and apparel industry. The research design included a quantitative method to evaluate the conceptual framework. Data were collected using random sampling and a structured survey questionnaire from important stakeholders of the textile and apparel industry, yielding 282 answers from industry leaders and followers. We utilized PLS-SEM to analyze the data and assessed the measurement model and structural model for hypothesis testing. Empirical results revealed that training satisfaction is positively related to organizational performance. Furthermore, findings also demonstrated that employee work engagement and job satisfaction are positively related to organizational performance. In addition to that, employee work engagement and job satisfaction positively mediate the relationship between training satisfaction and organizational performance. Training has long been regarded as a significant factor in establishing favorable employee attitudes and behaviors. This research reaffirms these ideas and emphasizes the significance of TS as a crucial factor in enhancing employee work engagement, job satisfaction, and organizational performance. Therefore, the findings of this investigation have many implications for researchers and professionals in human resource development in the textile organization. This research provides a noteworthy theoretical contribution to the existing literature by bridging the knowledge gaps and being the first to establish the importance of training satisfaction and the mediation impacts of employee work engagement and job satisfaction in enhancing organizational performance. Moreover, research offers practical implications as an empirical foundation for human resource executives and practitioners, particularly textile organizations.